Saúde mental e sintomas de Burnout entre operadores de Call Center - Xavier, Nelmelice (2023)
Introduction: Working is a central occupation in people's lives; it is a significant factor in the construction of identities and social insertion, but this may not always be professionally satisfying and may lead to emotional distress as well as dissatisfaction. Therefore, this research aims at collecting data to help understand this information and possible means of intervention, which could contribute to the organizational community and anyone else who might benefit from this. Objective: To assess symptoms of anxiety, depression and burnout in call center professionals. Methodology: This is a descriptive, quantitative survey. Data were obtained through an analysis of the inventories applied to 100 telemarketing operators from a Call Center company in the interior of São Paulo. The interviewees were assessed using the following instruments: a semi-structured interview; drawn up by the researchers, with 14 questions containing socio-demographic and socio-economic data and everyday situations experienced by telemarketing operators; Maslach Burnout Inventory (DASS-21) comprising 22 questions with seven-point Likert scale response options; Self Report Questionnaire (SRQ-20): 20 questions to identify the presence of common mental disorders. Results: The results showed an important impact on the presence of mental disorders in female employees. Considerations: Data showed a high presence of overload and stress among call center operators, especially,in women. It is important to modify working conditions and organizations in order to prevent the mental health of this population.